(untitled) (NTU Journal of Agriculture and Veterinary Science, 2021)
The results of the current study showed that the first appearance of Tetranychus urticae on the leaves of tomato plants in the field was on 7/14/2020 and that the highest average number of mites was on 17/8/2020 (371.78) individuals/10 leaves, while the lowest average for these numbers was recorded on 5 /10 (23.19 individuals), and the highest average of these numbers was on the Nabaa variety (240.05 individuals), while the lowest average of these numbers was recorded on the local variety (102.26 individuals). The correlation was positive and significant between the number of mites and the average weekly temperature (0.750) * and significant negative (0.685 * -) with the relative humidity. The lowest mean of infestation was on the tomato cultivars Sandra (69.97%) and GS (63.05%). Based on the criteria of % of infested leaves and mite population density, the tomato cultivars GS and local were the least sensitive to infection, respectively. The correlation values were insignificantly negative between of the affected leaves and the content of these leaves of proteins (-0.262), carbohydrates (-0.476) and flavonoids (-0.221), while it was significant positive with phenols (0.751) and insignificantly positive with alkaloids (0.432).